2018
DOI: 10.4178/epih.e2018018
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and associated factors among the elderly living in rural Chiang Rai, northern Thailand

Abstract: OBJECTIVESThis study aimed to characterize the prevalence of poor sleep quality and to identify associated factors among community-dwelling elderly individuals in northern Thailand.METHODSA cross-sectional study was conducted among 266 randomly selected elderly people in a sub-district in rural Chiang Rai Province, northern Thailand. The participants were interviewed using the Thai version of the Pittsburgh Sleep Quality Index (PSQI).RESULTSRoughly 44.0% of the participants had poor sleep quality (PSQI score, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
39
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 31 publications
12
39
2
5
Order By: Relevance
“…To alleviate the personal suffering and adverse effects introduced by poor sleep quality, it is essential to understand its prevalence pattern and associated factors. Previous studies have demonstrated many factors related to poor sleep quality among older adults, including but not limited to the following four domains: (1) socio-demographic factors, such as age [9], marital status [18] and education [19]; (2) lifestyle factors, such as physical activity [20] and caffeine intake [21]; (3) emotional factors, such as stress [22] and depression [20]; and (4) chronic conditions, such as arthritis [9] and pulmonary disease [23]. However, few studies have examined the prevalence and risk factors of poor sleep quality in a nursing home population.…”
Section: Introductionmentioning
confidence: 99%
“…To alleviate the personal suffering and adverse effects introduced by poor sleep quality, it is essential to understand its prevalence pattern and associated factors. Previous studies have demonstrated many factors related to poor sleep quality among older adults, including but not limited to the following four domains: (1) socio-demographic factors, such as age [9], marital status [18] and education [19]; (2) lifestyle factors, such as physical activity [20] and caffeine intake [21]; (3) emotional factors, such as stress [22] and depression [20]; and (4) chronic conditions, such as arthritis [9] and pulmonary disease [23]. However, few studies have examined the prevalence and risk factors of poor sleep quality in a nursing home population.…”
Section: Introductionmentioning
confidence: 99%
“…Most participants reported minimal general anxiety, however some 15-21% in both groups reported "fairly bad" sleep quality. Sleep quality and depression are common in the elderly [23]. While the analysis of sleep quality in our participants was beyond the scope of our study, these findings suggest that strategies to target sleep quality may be indicated given poor sleep hygiene is an independent correlate of NCD risk.…”
Section: Discussionmentioning
confidence: 91%
“…Whereas in men, sleep quality decrease continuously during the ageing process. 21 The previous study by Thichumpa, et al (2018) reported that 44% elderly (≥ 60 years) had poor sleep quality. Sleep problems that commonly experienced including getting up to the bathroom, waking up in the middle of the night or early morning, and difficulty falling asleep within 30 minutes.…”
Section: Discussionmentioning
confidence: 98%
“…Sleep problems that commonly experienced including getting up to the bathroom, waking up in the middle of the night or early morning, and difficulty falling asleep within 30 minutes. 22 Poor sleep quality was the most frequently found in patients attending primary health care. This condition might be caused by their perceived complaints, uncertain diagnosis, and fear about the prognosis of the disease.…”
Section: Discussionmentioning
confidence: 99%